2009
DOI: 10.1210/en.2008-1118
|View full text |Cite
|
Sign up to set email alerts
|

Lean Phenotype and Resistance to Diet-Induced Obesity in Vitamin D Receptor Knockout Mice Correlates with Induction of Uncoupling Protein-1 in White Adipose Tissue

Abstract: Increased adiposity is a feature of aging in both mice and humans, but the molecular mechanisms underlying age-related changes in adipose tissue stores remain unclear. In previous studies, we noted that 18-month-old normocalcemic vitamin D receptor (VDR) knockout (VDRKO) mice exhibited atrophy of the mammary adipose compartment relative to wild-type (WT) littermates, suggesting a role for VDR in adiposity. Here we monitored body fat depots, food intake, metabolic factors, and gene expression in WT and VDRKO mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
198
4
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(237 citation statements)
references
References 35 publications
21
198
4
7
Order By: Relevance
“…The vitamin D receptor is expressed in both white and brown adipocytes, and vitamin D and its metabolites are stored in adipose tissue. 21 Other recent studies demonstrated that the 1,25(OH)2D3 regulated, secreted bone protein osteocalcin mediates effects on adipose tissue, β-cells, and energy metabolism. 22 Researchers have reported that vitamin D3 supplementation during weight loss did not increase weight loss or associated factors compared with placebo; however, women who became replete experienced greater improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin D receptor is expressed in both white and brown adipocytes, and vitamin D and its metabolites are stored in adipose tissue. 21 Other recent studies demonstrated that the 1,25(OH)2D3 regulated, secreted bone protein osteocalcin mediates effects on adipose tissue, β-cells, and energy metabolism. 22 Researchers have reported that vitamin D3 supplementation during weight loss did not increase weight loss or associated factors compared with placebo; however, women who became replete experienced greater improvements.…”
Section: Discussionmentioning
confidence: 99%
“…UCP1, which is a highly specific marker for brown adipocytes and mediates the dissociation of cellular respiration from energy production, was elevated more than 25-fold in VDRKO white adipocyte tissue. This elevated UCP1 coincided with a resistance to high-fat diet-induced weigh gain in VDRKO mice [63]. This study identified a novel role of VDR on lipid accumulation and gene expression in adipose tissue.…”
Section: Role Of Vitamin Dmentioning
confidence: 58%
“…1α-hydroxylase has been reported to be expressed in adipose tissue and is functional in cultured adipocytes [62]. Interestingly, mice lacking CYP27B1 display a lean phenotype that is similar to hypoleptinemia and hyperphagia [63]. Leptin is an obesity-related gene product that is secreted by adipocytes.…”
Section: Direct Effectsmentioning
confidence: 99%
“…However, variation of wBAT without a corresponding variation in iBAT occurs in inbred strains of mice with spontaneous variant alleles, 20,21 in transgenic mice in which inactivation of raptor in adipocytes by Febp4-Cre recombinase (aP2-Cre) leads to induction of brown adipocytes in white fat depots, without an effect on iBAT; similarly, inactivation of the gene encoding the vitamin D receptor leads to a strong induction of uncoupling protein-1 (Ucp1) in white fat depots. 22,23 These models have provided strong evidence that mice with an elevated expression of wBAT are resistant to diet-induced obesity. Given the specificity of myf5 and PR-domain containing-16 (PRDM16) in determining the iBAT lineage, it is possible that variation in iBAT could be achieved independent of wBAT by manipulation of these genes.…”
Section: Diffuse Brown Adipocytes In White Fat Depotsmentioning
confidence: 99%